Miescher's granulomatosis (granulomatosis disciformis chronica et progressiva) in a non-diabetic patient - case report - Brzezińska-Wcisło Ligia; Bergler-Czop Beata; Rogala-Poborska Iwona (BMC, 2009)
Abstract Introduction Necrobiosis lipoidica diabeticorum is a rare disease of unclear etiology, that occurs in about 1% of diabetic patients. Case report We present case of granulomatosis disciformis chronica et progressiva Miescher with good response to systemic corticosteroids therapy. Patient 45 years old woman, with primary yellow-brown areas skin lesions, with foci well separated from surroundings on both lower legs, that occurred 5 years ago. In laboratory tests there was no abnormalities. Because of advance suggestion (after last admit in dermatological ward) of observation according to xantogranuloma necrobioticum tests for paraproteinemia were made. Immunoelectrophoresis, IgG, IgM, IgA levels, kappa light chain, lambda heavy chain; were correct, Bence-Johns protein-negative. During hospitalization in Clinic methylprednisolone in dose of 32 mg od, vascular drugs and local steroidotherapy was applied with good therapeutic response. Conclusion We described case of typical clinical and histological characters of necrobiosis lipoidica. without diabetes-granulomatosis disciformis chronica et progressiva Miescher that despite of suspicion of proper diagnosis for a long time was not treat effective.